ABUNDANCE AND DIVERSITY OF PHYTOPLANKTON IN RIVER FLOWS IN BANJAREJO VILLAGE IN SUPPORTING THE PRODUCTIVITY OF TRADITIONAL PONDS IN BANJAREJO VILLAGE, LAMONGAN - Nurvita, Aprillia Dwi; Laila, Nur Roudlotul; Isroni, Wahyu; Dewi, Nina Nurmalia (Journal of Aquaculture Development and Environment, 2024)
Banjarejo Village River close by in a way direct with aquaculture areas so that the main water source used for irrigate pond originate from river water. Problems in the Banjarejo Village River is lack of management waste domestic nor waste activity agriculture can influence water quality and existence phytoplankton. Therefore that's the goal study this for know composition type, abundance, diversity, uniformity and dominance phytoplankton in rivers as material information management pond traditional and River. Taking sample done month December 2023 and January 2024 at time morning, afternoon and evening. Research sites found 3 stations. The main parameters observed covers abundance, diversity, uniformity and dominance phytoplankton. Meanwhile, the supporting parameters in the form of bulk data rain and water quality. Composition results type phytoplankton found in the Banjarejo Village River as many as 17 genera from 4 classes phytoplankton (Bacillariophyceae, Chlorophyceae, Cyanophyceae and Xanthophyceae). The value of abundance phytoplankton in the river flow in Banjarejo Village in the month December and January are included in type waters mesotrophic, index diversity medium, index even uniformity, and index dominance show that no there is a genus that dominates. Brightness, ammonia, nitrate and nitrite values in December and January overall exceeded the maximum limit. As for the test results of other parameters like temperature, DO, pH, salinity and phosphate still in optimal category for growth phytoplankton.